Reliability of Several Glaucoma Tests in Patients With Boston Type 1 Keratoprosthesis. Issue 3 (16th March 2022) - Akpek, Esen K.; Karakus, Sezen; Yohannan, Jithin; Jabbour, Samir; Sotimehin, Ayodeji E.; Li, Gavin; Ramulu, Pradeep Y.
Abstract : Purpose: Managing glaucoma after Boston type 1 keratoprosthesis (KPro) surgery remains challenging. We herein assessed the fitness of commonly used clinical tests to evaluate glaucoma in KPro eyes versus eyes with penetrating keratoplasty (PK) as controls. Methods: Sixteen patients with KPro and 14 patients with PK tested in an identical manner. After the 10-2 visual field with size V stimulus, intraocular pressure (IOP) was estimated with palpation by the first observer. Then, retinal nerve fiber layer (RNFL) thickness analysis was performed twice using optical coherence tomography by an ophthalmic photographer, before and after a short break. After the second observer estimated the IOP, the visual field was repeated. Finally, color photographs of the optic disk were captured by an ophthalmic photographer. The cup-to-disk ratio was assessed by 2 masked observers, at 2 different time points, in a random manner. Agreements between and within observers and reliability of repeated measurements were evaluated using the intraclass correlation coefficient (ICC) and Bland–Altman plots. Results: Inter-rater agreement of palpation IOP estimate was moderate for eyes with KPro (ICC = 0.47) and fair for eyes with PK (ICC = 0.27). Visual field and RNFL thickness showed high test–retest reliability in both KPro and PK eyes (ICC > 0.80 for both). Inter-rater agreement of cup-to-disk ratio assessments was substantial in eyes with both KPro (ICC = 0.62) and PK (ICC = 0.70). Conclusions: The 10-2 visual field and RNFL thickness seem sufficiently repeatable and might allow the detection of glaucoma progression in KPro eyes. Such testing is important, given limited inter-rater agreement regarding the palpation IOP estimate.